2-Alkylation of 3-Alkyindoles With Unactivated Alkenes - Pan, Xuling; Liu, Qian; Nong, Yingling (Frontiers in Chemistry, 2022)
An acid-catalyzed 2-alkylation of indole molecules is developed. Only catalytic amount of the commercially available, inexpensive and traceless HI is used as the sole reaction promoter. 2,3-Disubstituted indole molecules bearing congested tertiary carbon centers are afforded as the final products in moderate to excellent yields.